Lecture Notes in Networks and Systems: Intelligent Manufacturing and Mechatronics - Wan Hasbullah, Mohd Isa (Springer Singapore, 2024)
We are pleased to present the proceedings of the fourth edition forum of The Innova-tive Manufacturing, Mechatronics and Materials Forum 2023 (iM3F 2023), organized by Universiti Malaysia Pahang Al-Sultan Abdullah through its Faculty of Manu-facturing and Mechatronic Engineering Technology. The conference took place on August 7th and 8th, 2023, with a primary focus on manufacturing, mechatronics, and materials. During iM3F 2023, we received a total of 70 submissions for mechatronics and partially manufacturing tracks, which underwent a rigorous single-blind review process. Our dedicated reviewers recommended 50 papers for publication in this Springer Proceedings of Materials. We extend our sincere gratitude to all the authors who contributed their valuable research to this volume. The papers included in this proceeding have undergone thorough evaluation by our esteemed technical review committee, comprising experts in the fields of materials and manufacturing engineering. The conference provided a platform for the exchange of cutting-edge insights, highlighted by keynote speeches from distinguished speakers, including Assoc. Prof. Ir. Dr. Haji Nik Mohd Zuki Nik Mohamed (Universiti Malaysia Pahang Al-Sultan Abdullah, Malaysia), Prof. Eng Hwa Yap (Xi’an Jiaotong-Liverpool University, China), and Prof. Gian Antonio Susto (Universita Degli Studi, Italy).